Numerical Simulation of the Stress Field in Repeated Mining of Coal Seams Based on In Situ Stress Measurement. (9th November 2021) - Yang, Donghui; Yang, Bohu; Lv, Zhaoheng; Li, Yongming; Cheng, Hongming; Ning, Zhangxuan
Abstract : We established an evaluation index of the rock mass stress state for underground coal mines using the strength-stress ratio based on the measured in situ stress and the generalized Hoek–Brown strength criterion. Three in situ stress states, σ cm / σ 1 m  < 1.4 (high), 1.4 <  σ cm / σ 1 m  < 3.6 (medium), and σ cm / σ 1 m  > 3.6 (low), were established based on the value of the unconfined compressive strength ( σ cm ) and the maximum principal stress of the rock mass ( σ 1 m ). This index classifies the Burtai mine as a medium-high in situ stress field, which is in agreement with the on-site situation, establishing the reliability of the index. The working face was a three-dimensional geological model based on the log sheets. The initial conditions for the model were determined using the combined measurements of the in situ stress regression model. We performed numerical simulations of the roof stress field distribution under repeated mining. Mining the overlying coal seam leads to significant variation in the value and direction of the main roof, σ 1, within the range of the front abutment pressure under the pillar and gob. Along the main roof strike direction, σ 1 under the pillar is 1.5 times that under the gob, and the σ 1 direction under the pillar is deflected by 5°, which is 30° smaller than that under the gob. This provides a reference for optimized underground coal mining.